2018
DOI: 10.1044/2018_ajslp-17-0222
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Velopharyngeal Dysfunction: Survey, Literature Review, and Clinical Recommendations

Abstract: Clinical uncertainty among speech-language pathologists surveyed and the paucity of published clinical guidelines for assessing individuals with AVPD indicate the need for additional clinical research for this disorder, one that is heterogeneous and distinct from those with congenital velopharyngeal dysfunction. The proposed evidence-based clinical worksheet may assist in determining management for patients with AVPD and may serve as a starting place for validation of a clinical guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…It is unknown if all recipients of the survey were eligible for the study; if all were indeed eligible, then the estimated response rate would be 21%, at a minimum. Hardin-Jones et al (2019) reported a response rate of 13%, and it was not possible to calculate the response rate in other survey studies related to CL/P (eg, Kummer et al, 2011; Guyton et al, 2018), given the very specific intended recipients for these types of surveys. It would also be of interest to learn more specifically about the content and quality of information that families’ service providers provide to them about their child’s literacy.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown if all recipients of the survey were eligible for the study; if all were indeed eligible, then the estimated response rate would be 21%, at a minimum. Hardin-Jones et al (2019) reported a response rate of 13%, and it was not possible to calculate the response rate in other survey studies related to CL/P (eg, Kummer et al, 2011; Guyton et al, 2018), given the very specific intended recipients for these types of surveys. It would also be of interest to learn more specifically about the content and quality of information that families’ service providers provide to them about their child’s literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there are formal guidelines available for instrumental assessment of voice, 84 and acquired velopharyngeal dysfunction. 85 However, those seeking guidelines pertaining to intervention in the areas of speech, language and literacy development, either in person or in a virtual model, may have to rely on general position papers from regulatory bodies, which often do not provide concrete practice recommendations, or individual research studies, which are often based on specific populations, limiting practice generalizability. Those working as clinicians and as researchers in the field of speech-language pathology would benefit from the development and dissemination of additional CPGs addressing topics from developmental and medical sectors of the field.…”
Section: Future Directionsmentioning
confidence: 99%
“…Currently, those working in the medical sector, have access to select Clinical Practice Guidelines to inform certain aspects of their practice. Specifically, there are formal guidelines available for instrumental assessment of voice (Patel et al, 2018) and acquired velopharyngeal dysfunction (Guyton et al, 2018).…”
Section: Standardized Assessment Recommendations In Virtual Carementioning
confidence: 99%
“…Specifically, there are formal guidelines available for instrumental assessment of voice, 86 and acquired velopharyngeal dysfunction. 87 However, those seeking guidelines pertaining to intervention in the areas of It should also be noted that the majority of available standardized tools were developed for in person-use with monolingual-English speaking children. These standardized normreferenced assessments are a valuable tool but are not the singular method of evaluating the language and literacy skills of school-aged children, particularly for children from linguistically and culturally diverse backgrounds whose English language skills often differ from their monolingual English peers.…”
Section: Future Directionsmentioning
confidence: 99%